Ionic Liquid-Enhanced Assembly of Nanomaterials for Highly Stable Flexible Transparent Electrodes - Jianmin Yang; Li Chang; Xiqi Zhang; Ziquan Cao; Lei Jiang (Nano-Micro Letters, 2024)
Highlights We present a method that utilizes ionic liquid-enhanced nanomaterial assembly to fabricate highly stable and large-area MXene-silver nanowire electrodes with ordered layered structures. This approach emphasizes the use of hydrophobic and nonvolatile ionic liquids, which form stable interfaces with water by reducing interface energy, preventing the sedimentation loss of nanomaterials during assembly. The prepared electrodes not only exhibit excellent optoelectronic properties (9.4 Ω sq−1 sheet resistance and 93% transmittance), but also have exceptional antioxidant capacity.